2004
DOI: 10.1002/chin.200433069
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Limitations of Lithium‐Ethylenediamine—THF‐Mediated Cleavage at the α‐Position of Aromatics: Deprotection of Aryl Methyl Ethers and Benzyl Ethers under Mild Conditions.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…This is consistent with the known mechanism in which electron-rich arenes cannot accept the second electron unless the radical anion intermediate is protonated to form the corresponding radical species ( 31 ). Also, we did not observe any of the dealkylated phenol by-product that was reported in the method developed by Sugai ( 25 ). With methanol, ethanol, isopropanol, t -butanol, ( 2 , 32 ) and t -amyl alcohol, diene 4 was produced in 33, 58, 62, 75, and 68% yields, respectively, with the over-reduced product 5 in 4 to 11% yields (entries 2 to 6).…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…This is consistent with the known mechanism in which electron-rich arenes cannot accept the second electron unless the radical anion intermediate is protonated to form the corresponding radical species ( 31 ). Also, we did not observe any of the dealkylated phenol by-product that was reported in the method developed by Sugai ( 25 ). With methanol, ethanol, isopropanol, t -butanol, ( 2 , 32 ) and t -amyl alcohol, diene 4 was produced in 33, 58, 62, 75, and 68% yields, respectively, with the over-reduced product 5 in 4 to 11% yields (entries 2 to 6).…”
contrasting
confidence: 48%
“…Their 0.45-mol scale reaction took 3 days in a flow reactor without tri(pyrrolidin-1-yl)phosphine oxide ( 13 ). The Sugai group treated arenes with lithium and ethylenediamine in tetrahydrofuran (THF) or Et 2 O but did not isolate 1,4-cyclohexadiene products ( 25 , 26 ) and indicated that THF might be a ligand for a lithium ion ( 25 ).…”
mentioning
confidence: 99%